Judicial Independence vis-à-vis Judicial Populism: the Case of Ulayat Rights and Educational Rights - Rosa Ristawati; Radian Salman (The Constitutional Court of the Republic of Indonesia, 2020)
Judicial populism may occur when judicial branches are much more influenced by the interest of people majority. In this context, it is when justices deliver decisions according to what the people wanted and not what it has to be decided by laws. The Constitutional Court of the Republic of Indonesia (MKRI) has the pivotal role to protect the Constitution, democracy, and the rule of law principles by adhering judicial independence in the decision making process. This paper aims to briefly find out whether the MKRI decisions on the particular issue of economic and social rights show the tendency of judicial populism and defending judicial independence. A brief conclusion would be drawn from the analysis of the two MKRI’s landmark decisions on the relevant issues of economic and social rights, in particular issues of Ulayat rights and educational rights (Case Number 35/PUU-X/2012 on the judicial review of Law No. 41 of 1999 on the Forest and Case Number No. 13/PUU-VII/2008 on the judicial review of Law No. 16 of 2008 on the Amendment of the Law No. 45/2007 on the State Budget). In a short analysis of both landmark decisions, the MKRI tends to defend its independence in delivering its decision. The Court also shows its consistency in protecting the Constitution by strictly upholding the constitutional values laid down in the Constitution and against the judicial populism. The Court in both decisions shows its constitutional commitment to preserving democratic values of minority-marginalized protection against the dominant-majoritarian interest. In the particular issue of education rights, the Court hinders the fulfilment of educational rights from the elite interest by preserving the constitutional purpose of making priority 20% for the education budget. In general, the MKRI has to guard preventing the Constitution and the rule of law principles, specifically on the issue of the protection of economic-social rights. It upholds judicial independence and put asides judicial populism.